A comparison of susceptibility to stocks of Trypanosoma simiae of Glossina pallidipes originating from allopatric populations in Kenya - Moloo, S.K.; Zweygarth, E.; Sabwa, C.L. (Wiley, 1995)
A colony of Glossina pallidipes with originated from Nguruman, Rift Valley Province. Kenya, was significantly more susceptible than a colony of the same species which originated from Shimba Hills. Cost Province, Kenya, to infection with a stock of Trypanosoma simiae CP 11 isolated from wild G. austeni in Coast Province, Kenya, irrespective of whether pigs or goats were used as infecting hosts. Male G. pallidipes from both the colonies were more susceptible than females to this T. simiae stock. Similarly, a G. pallidipes colony of Nguruman origin was significantly more susceptible than the colony of Shimba Hills origin to infection with another stock of T. simiae CP 813 isolated from wild G. pallidipes in Coast Province, Kenya, again irrespective of whether pigs or goats were used as infecting hosts. The susceptibility of the sexes of G. pallidipes from both the colonies to T. simiae CO 813 did not differ significantly when pigs were used as infecting hosts, but male G. pallidipes from both the colonies were significantly more susceptible than female tsetse to this T. simiae stock when goats were used as infecting hosts. Nevertheless, if the observed differences in susceptibility of the two G. pallidipes colonies reflect transmission of trypanosomes by the two allopatric populations of tsetse in the field, then the epidemiology of simiae trypanosomiasis probably differs between these two areas of Kenya.